The computational analysis and geo spatial the water resources of the Port Complex of PecÃm - Fernando AntÃnio Costa Pereira (2014)
The present work has for objective to use a model of analysis of computational tools and tabular georeferencing as instruments to diagnose and analyze the water balance of the whole system which meets the Port Complex of PecÃm â CPP, In order to provide support in decision making forward the critical events and to give guarantees of supply of raw water in quantity and quality for the multiple users already signed and with a forecast of new concessions within the Port Complex PecÃm. Through computational analysis and geo spatial, both of water sources as well as of the users connected to the water resources of the CPP, and with the measurement of some hydraulic information, mainly flow effectively consumed and flow grantee, you can draw as well, a diagram that shows the vulnerability or not this water system and the possible alternatives for solutions to avoid the undersupply of the Port Complex of Pecem, as well as show the prospect of water supply for the care of future water demand from the strategic planning and the study and projects of socio economic development for this important region. Thus, it is expected to develop an efficient network that holds the most different hydraulic structures, to allow the generation of more various scenarios involving the water balance and the security of supply of water to the Port Complex PecÃm.